Using Media by Nurses: A Case of Novel Coronavirus Disease - Abdulsamed Kaya; Arzu Kader Harmancı Seren (Association of Nurse Managers, 2021)
The term 'media' used to explain the mass media provides the transmission of messages and information regarding the society. According to the researches, media has an important power in influencing the masses in terms of public interests and policies. By addressing the media as a priority, through individual or professional organizations, nurses can be effective in exposing the profession's image in the media and policy issues affecting the profession. A more consistent approach to presenting nursing research to the public and using the media for this purpose will enable the public to perceive nursing as it is and support the use of research. In this review, basic knowledge tried to be provided by the nurses about what to do through the media and, the actions taken in the media related to the novel coronavirus disease which emerged first at the end of 2019 in Wuhan Province of China and in March 2020 in Turkey, were examined.